A Phase II Study of Denileukin Diftitox in Patients with Advanced Treatment Refractory Breast Cancer - William R. Gwin; Lupe G. Salazar; James Y. Dai; Doreen Higgins; Andrew L. Coveler; Jennifer S. Childs; Rosie Blancas; Yushe Dang; Jessica Reichow; Meredith Slota; Hailing Lu; Mary L. Disis (Vaccines)
Background/Objectives: Regulatory T cells (Treg) suppress immunity in the tumor microenvironment, are linked to poor prognosis across breast cancer subtypes, and suppress the cytolytic function of cytotoxic CD8+ T cells. Denileukin diftitox, a diphtheria toxin (DT)/IL-2 fusion protein, targets and depletes Tregs. This Phase II study aimed to assess the safety of denileukin diftitox and its effect on Tregs and tumor growth in patients with advanced breast cancer. Methods: This single-arm Phase II study of denileukin diftitox enrolled patients with refractory stage IV breast cancer. Patients received denileukin diftitox 18 mcg/kg/day IV for Days 1–5 every 21 days for up to six cycles. Toxicity was assessed using CTCAE v3.0 and tumor response was evaluated per RECIST criteria. Blood samples were collected to analyze Tregs by flow cytometry and anti-DT antibodies by ELISA. Results: Fifteen patients with stage IV breast cancer were enrolled. Four patients completed all planned denileukin diftitox infusions and achieved stable disease (27%, 95% CI [0.08, 0.55]). Two patients (13%) discontinued due to toxicity, and nine patients (60%) discontinued due to progressive disease. Eleven patients experienced at least one grade 3 or 4 adverse event. Although there was a general reduction in peripheral blood Tregs, the difference in CD4+CD25+FOXP3+ Tregs levels post-treatment was not statistically significant (p = 0.10). Six patients (40%) achieved <semantics>≥</semantics>25% reductions in Tregs. A significant increase in anti-DT IgG antibodies was observed post-treatment (p < 0.005). Conclusions: Denileukin diftitox demonstrated moderate toxicity in this advanced breast cancer cohort. Denileukin diftitox modulated regulatory T cells. However, the majority of patients experienced disease progression in the study.